2013
DOI: 10.1177/0049475513480771
|View full text |Cite
|
Sign up to set email alerts
|

Subacute intestinal obstruction: an enigma revisited

Abstract: Sixty-three patients presenting with subacute intestinal obstruction (SAIO) were studied. Thirty (47.6%) reported recurrent symptoms. Exaggerated bowel sound, visible/palpable bowel loops, distention of abdomen and abdominal lumps were observed in 60.3%, 28.5%, 25.3% and 19.0% patients, respectively. Thirty (47.6%) required emergency laparotomy. Investigations revealed lesions requiring surgery in 14 of 33 patients which were relieved with conservative treatment. The accuracy of ultrasonography, contrast enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
(14 reference statements)
1
5
1
Order By: Relevance
“…Out of which 40% patients (40%) had laparotomy for gynecological conditions while 33.33% patients had open appendectomy and 16.67% had undergone colorectal surgeries. In a others studies about 50% and 32% patients had undergone previous abdominal surgery 11 which is less when compared to ours.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Out of which 40% patients (40%) had laparotomy for gynecological conditions while 33.33% patients had open appendectomy and 16.67% had undergone colorectal surgeries. In a others studies about 50% and 32% patients had undergone previous abdominal surgery 11 which is less when compared to ours.…”
Section: Discussioncontrasting
confidence: 75%
“…In our study abdominal distention was present among 32% patients which comparable to finding in another study which was 28.5%. 11 It was found that abdominal tenderness was present among (8/50) 16% patients and most of them 6 out of 8 underwent laparotomy with resection and anastomosis. Therefore, patients who have abdominal tenderness must be monitored carefully as there are increased chances of operative interventions in these groups of people.…”
Section: Discussionmentioning
confidence: 96%
“…Shaikhet al reported these strictures in 8.3% of their patients with intestinal obstruction [ 27 ]. A recent study from India has reported these strictures to be the cause in 27.2% although the exact cause is not known ischaemia might be the most common etiology with most strictures localized to ileum and jejunum [ 28 ]. Lalwani et al from our department have also shown the ileum to be the most common site in patients with post-traumatic strictures which probably develop after the segmental blood supply is compromised due to injury to the mesenteric vessels [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from India has reported these strictures to be the cause in 27.2% although the exact cause is not known ischemia might be the most common etiology with most strictures localized to ileum and jejunum. [27] Lalwani et al from our department have also shown the ileum to be the most common site in patients with post-traumatic strictures which probably develop after the segmental blood supply is compromised after injury to the mesenteric vessels. [28] Since malignancy was a frequent cause, adjuvant radiation treatment was responsible for strictures in 12 patients.…”
Section: Discussionmentioning
confidence: 94%